STUDY OF VOC EMISSIONS AND ODOURS FROM FOAM MATERIALS IN FURNITURE PRODUCTION (Innovation in Woodworking Industry and Engineering design, 2026)
The issue of volatile organic compounds (VOCs), odours or smells emitted from materials is researched in terms of our environment and human health. The Department of Furniture at Mendel University in Brno has been dealing with this subject for a long time. Main direction of this research is defined by composition of quantitative and qualitative emissions of VOCs which are emitted into the air from chosen materials used in the manufacturing of upholstered furniture such as polyurethane foams and latex rubber. Emission measurement is determined in space chamber with pre-defined conditions. This methodology is described in the standard ČSN EN ISO 16 000-9. The samples of air from the climate chamber, where the test sample is placed, are then analyzed by gas chromatography (GC) on a gas chromatograph with mass spectrometer and thermal desorption. Another part of this research is olfactometric assessment of odours emitted from tested materials, by the indirect olfactometry method. The relevance of the individual components on emissions of odour intensity and hedonic effect will be determined according to the chemical analyses of the achieved results. This study investigates the problem of VOC emissions and odours emitted from polyurethane foam, viscoelastic foam and latex at the temperature of 23 °C and a relative humidity of 50 %. The time aspect in connection with the amount of volatile organic compounds released to the air are examined in this document. Particularly it was pointed on the identification of substances which release from these foams. These substances express the characteristics of the foam materials from the point of the release of volatile organic compounds and odours.